Rekayasa Sistem Pendukung Keputusan Dengan Algoritma ID3 Dalam Penentuan Jurusan Akademik (Studi Kasus : SMA Negeri 3 Ngajuk) - Prasetiyo, Rinto; Sujatmiko, Bambang; Ali, Mahrus (Inovate, 2022)
Designation is the process of selecting and determining the interest of students in the subject area or skill competency offered by the education unit. The majors process at SMA Negeri 3 Nganjuk begins when the student has been accepted by the school, after which the student takes a major test. In the majors at SMA Negeri 3 Nganjuk, the majors process still uses Microsoft Excel so it takes a long time for majoring students. Because of that, we need a system that can process students effectively and efficiently. The ID3 algorithm is widely used to solve various majors problems. The solution in the ID3 algorithm is based on mathematical calculations that determine the entropy and gain values ​​used in the formation of a decision tree. The ID3 algorithm produces a decision tree that is good enough to be used in majors because this algorithm can solve multi-criteria and multi-objective problems. The results of this study indicate that the manual calculation needs to be shortened in the calculation of the program so that it can produce a majors flow. If it is not shortened it will result in an error in the program. The results of calculating 100 sample data in the first result produce a total entropy of 0.8813, in the second calculation it produces a total entropy of 0.9403, in the third calculation it produces a total entropy of 0.9367. After that a rule is formed which is used as a benchmark for student majors. The final result of the majors shows that the students' scores resulted in more students entering the social studies department than the Mathematics and Natural Sciences majors. Keywords: Pointing, Value, ID3 Algorithm